Opinion Piece. Holistic Homeopathic Approach to Delayed Milestones in Children: A Miasmatic and Constitutional Viewpoint. - Parikh, Namrata; Mulla, Muddassir M. (Homoeopathic Heritage, 2026)
Developmental delays in children are becoming increasingly common, often presenting as delayed speech, walking, or social interaction. While conventional medicine provides therapeutic exercises and developmental monitoring, homeopathy offers a curative approach by addressing underlying miasmatic influences and constitutional imbalances. This article explores the homeopathic understanding of delayed milestones with a real-life case demonstrating the role of individualized prescriptions in promoting holistic development.